PENGEMBANGAN BAHAN AJAR KASAJANG BERBASIS ICT UNTUK MENINGKATKAN KEMAMPUAN LITERASI NUMERASI ABAD 21 - Fikriyyah, Faridatul; Miftachudin; Desi Setiyadi (Faculty of Educational Sciences,Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2025)
This study is motivated by the low numeracy literacy skills of students in solving mathematical problems contained in the unit length conversion material and the lack of technology utilization in teaching materials in the classroom. One solution to overcome these problems is to develop teaching materials that integrate length unit conversion material through ICT-based kasajang teaching materials in mathematics learning. This research uses the RnD (Research and Deplopment) method with the ADDIE model in the form of Analysis, Design, Implementation, and Evalution stages. Data were collected through various techniques such as: observation, validation by a team of experts, student numeracy literacy tests, and assessment of the feasibility of teaching materials from teachers and students through interviews. The results showed that this ICT-based kasajang teaching material could meet the criteria of being very valid based on the assessment of 96% media expert validators, 100% material expert validators and 98% language expert validators. In addition, the results of the student numeracy literacy test increased after using this teaching material obtained from the comparison between the pre-test value and the pre-test value when using the kasajang teaching material. the results of the average difference using the kasajang teaching material show that the learning media is effective in improving 21st century numeracy literacy skills. Keywords: Kasajang Teaching Materials, ICT, Numeracy Literacy.